2023
DOI: 10.3389/fimmu.2022.1052692
|View full text |Cite
|
Sign up to set email alerts
|

PROS1 shapes the immune-suppressive tumor microenvironment and predicts poor prognosis in glioma

Abstract: BackgroundGlioma is the most malignant cancer in the brain. As a major vitamin-K-dependent protein in the central nervous system, PROS1 not only plays a vital role in blood coagulation, and some studies have found that it was associated with tumor immune infiltration. However, the prognostic significance of PROS1 in glioma and the underlying mechanism of PROS1 in shaping the tumor immune microenvironment (TIME) remains unclear.MethodsThe raw data (including RNA-seq, sgRNA-seq, clinicopathological variables and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…In contrast, these sites were accompanied by higher levels of M2 macrophage in ltration. As a subtype of macrophages, M2 macrophages typically promote cancer progression (41) as demonstrated in the current investigation. Indeed, this leads us to believe even more strongly that methylation and expression of HNRNPLL have independent effects on the development and progression of liver cancer.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, these sites were accompanied by higher levels of M2 macrophage in ltration. As a subtype of macrophages, M2 macrophages typically promote cancer progression (41) as demonstrated in the current investigation. Indeed, this leads us to believe even more strongly that methylation and expression of HNRNPLL have independent effects on the development and progression of liver cancer.…”
Section: Discussionsupporting
confidence: 64%
“…The SBC group was also enriched in genes related to the regulation of stress response, including f7i , sesn1 , pros1 , and pargl . Both f7i and pros1 are important clotting factors ( Wang et al, 2023 ; Ye et al, 2023 ). Furthermore, genes involved in cranial skeletal system development, such as hspg2 , pkn2a , pls3 , and usp18 , were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TF is related to epithelial-mesenchymal transition (EMT) and has the potential to become an effective target against EMT and thrombotic events in LGG. PROS1 , a vital blood coagulation gene, was considered to promote the glioma immunosuppressive microenvironment ( 80 ). In addition, another study showed PROS1 was enriched in complement activation in LGG, indicating the critical role of CCC in the progression of LGG ( 81 ).…”
Section: Discussionmentioning
confidence: 99%